ACCRUAL ACCOUNTING SYSTEM AND IDENTIFICATION OF BARRIERS TO ITS ESTABLISHMENT - Fatemeh Hazrati; Shihab Ibrahim Shuhaib; Mahmoud ebrahim Alrekabi; Maytham taha yaseen; Abbas Naser Enad Alali; Saad Dahham Abdulhussein (Scholar Express Journals, 2022)
Public sector accrual accountant in practice in the 1990s and the need to achieve the cost of services requires the use of accrual accounting basis in users of the public budget. Methodology: This research has been applied in terms of purpose, how to collect data qualitatively, and data collection tools in the form of in-depth specialized interviews of accrual accounting experts in three stages of open, centralized, and selective coding of data. The sampling method was a snowball. Obstacles identified as a model in three dimensions, components, and indicators tested by fuzzy triangular Delphi technique by 25 knowledgeable accrual accounting elites. Obstacles were also rated using the AHP technique and finally with cluster analysis, guidelines for establishing and implementing accrual accounting were provided.
Keywords: Operational budgeting; accrual accounting; cost accounting; public sector accounting